Ethics And Human Morality Communication As Social Responsibility - Nisa, Khairun; Ritonga, Mahzura Alfirah; Dinar, Yohani Putri; Ramadhan, Melja; Amri, Haikal Mohammad; Thariq, Muhammad Ibnu; Raihan, Muhammad Daffa; Habib, Muhammad Naufal (ProBisnis : Jurnal Manajemen, 2023)
The environment, especially family, plays a crucial role in shaping a person's communication ethics and morality. Modern life filled with technology and globalization demands awareness of the importance of ethics and morals in communication as the basis of human behavior. As time goes by, there is a visible decline in ethical awareness, which needs to be passed on to future generations. This research proposes three main questions, namely the role and influence of human ethics and morality in communication as people in social responsibility, the challenges faced in the modern era, and the opportunities that can be taken. Research methods involve a deep understanding of ethics and morality, with results and discussions highlighting the role of communication in social responsibility. This research recognizes that ethics and morality play a key role in shaping the character of individuals and society, especially in policy and regulation making. Amid the challenges of moral pluralism and technological risks, this research emphasizes the importance of awareness of ethics and morality in building healthy relationships, creating an inclusive communication environment, and supporting the development of a better society as a whole.